Animal Rights and Use of Animals in Biomedical Research - Rafique, Zoheb (Bangladesh Journal of Bioethics, 2015)
Experiments on animals have always been considered as necessary for scientific research, both fundamental and applied. In addition to scientific suitability criteria, this practice also must be justified from a moral point of view. This concern arises from the demand of our civilization that a certain moral value be recognized to animals. In this paper it is discussed in detail that how animals should be handled while doing research and what are animal rights and their uses in biomedical research. Bangladesh Journal of Bioethics 2015 Vol.6 (1):11-14